Developing of instructional media-based animation video on enzyme and metabolism material in senior high school - Yusuf, Muhammad Mustofa; Amin, Mohamad; Nugrahaningsih, Nugrahaningsih (Jurnal Pendidikan Biologi Indonesia, 2017)
The research aimed to product a learning material related to animation video on enzyme and metabolism material for high school student which is validated by media and material experts, educational practition and student legibility. Research and development model is ADDIE with quantitative-qualitative data analyzing methode. Data collection was obtained from validation results by media and material experts, educational partition and student legibility. The validation results were scores and suggestion. The percentage of product from expert media validation (100%), expert material validation (89,58%), educational practition (84,61%), and student legibility (81,91%) showed valid of the criteria and feasible to use after revision.